(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
Electrode behaviour of tellurium (IV) in the presence of different backgrounds has been studied. It has been shown that it is more preferable to carry the amperometric titration at +1 V by means of reagent oxidation current. It has been shown also that chemical interaction corresponds to the 1:4 molar ratio of the reacting components and takes place with reduction of tellurium (IV) to tellurium (II). Optimal conditions for determination: acidity, concentration ranges for tellurium, influence of accompanying ions have been revealed. Mathematic statistic treatment of obtained experimental data has been carried out.